Association of Recommended Food Score with Depression, Anxiety and Quality of Life in Korean Adult (P16-018-19) - Kim, Hyesook (Curr Dev Nutr, 2019)
OBJECTIVES: This study hypothesized that a higher diet quality score is associated with a lower observance of symptoms of depression and anxiety and a higher QoL. METHODS: This study Evaluated 1295 adults (521 men; 774 women) aged 19–64 years, who participated in the 2014–2015 National Fitness Award Project. Diet quality was measured by the recommended food score (RFS), and mental health and QoL were assessed by the Beck depression inventory (BDI), Beck anxiety inventory (BAI), and the World Health Organization QoL–Brief (WHOQoL–BREF). RESULTS: After adjusting for covariates, the individuals with depression had a significantly lower RFS value compared to those without depression, and the good QoL group had a higher RFS value than the poor QoL group. These trends occurred in both men and women. Subjects in the highest tertile of RFS showed a lower odds of depression (OR = 0.44, 95% CI = 0.29–0.68, P-trend = 0.0002) and poor QoL (OR = 0.35, 95% CI = 0.26–0.47, P-trend <0.0001) than those in the lowest tertile. There was no association of the RFS with anxiety. CONCLUSIONS: Our data suggest that improved diet quality is associated with lower ing depressive symptoms and a better QoL in Korean adults. FUNDING SOURCES: This study was supported by the Bio & Medical Technology Development Program funded by the Ministry of Science & ICT (2012M3A9C4048761) and Future Planning through the National Research Foundation (NRF) and Basic Science Research Program (NRF-2018R1C1B4A01023629) funded by the Ministry of Science, ICT, and Future Planning, Republic of Korea.